The Importance of Entomo-Virological Investigation of Yellow Fever Virus to Strengthen Surveillance in Brazil - Ana Cecília Ribeiro Cruz; Leonardo Henrique Almeida Hernández; Carine Fortes Aragão; Thito Yan Bezerra da Paz; Sandro Patroca da Silva; Fábio Silva da Silva; Ana Alice de Aquino; Glennda Juscely Galvão Pereira Cereja; Bruna Lais Sena do Nascimento; José Wilson Rosa Junior; Carmeci Natalina Elias; Cristiano Gomes Nogueira; et al. (Tropical Medicine and Infectious Disease, 2023)
The largest outbreak of sylvatic yellow fever virus (YFV) in eight decades was recorded in Brazil between 2016–2018. Besides human and NHP surveillance, the entomo-virological approach is considered as a complementary tool. For this study, a total of 2904 mosquitoes of the Aedes, Haemagogus and Sabethes genera were collected from six Brazilian states (Bahia, Goiás, Mato Grosso, Minas Gerais, Pará, and Tocantins) and grouped into 246 pools, which were tested for YFV using RT-qPCR. We detected 20 positive pools from Minas Gerais, 5 from Goiás, and 1 from Bahia, including 12 of Hg. janthinomys and 5 of Ae. albopictus. This is the first description of natural YFV infection in this species and warns of the likelihood of urban YFV re-emergence with Ae. albopictus as a potential bridge vector. Three YFV sequences from Hg. janthinomys from Goiás and one from Minas Gerais, as well as one from Ae. albopictus from Minas Gerais were clustered within the 2016–2018 outbreak clade, indicating YFV spread from Midwest and its infection in a main and likely novel bridging vector species. Entomo-virological surveillance is critical for YFV monitoring in Brazil, which could highlight the need to strengthen YFV surveillance, vaccination coverage, and vector control measures.